FINANCIAL PLANNING ANALYSIS AT THE PRINCIPAL CLINIC OF ANNISA BLORA TRANSITIONING TO MOTHER AND CHILD HOSPITAL - Gagah Baskara Adi Nugraha; Erliany Syaodih; Rian Andriani (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2024)
Objective – The research aims to assess the income, health facility levels, potential new funding sources, and financial planning policies at a Principal Clinic transitioning to a Mother and Child Hospital.Design/Methodology/Approach – This qualitative descriptive case study will be conducted from November 2023 to March 2024.Findings – The analysis indicates plans to collaborate with BPJS for funding. The income will be allocated for medical equipment procurement, and NPV analysis yielded a positive value of IDR 985,286,391, with a 4-year and 1.5-month payback period.Conclusion and Implications – Limited existing research on financial planning analysis for transitioning clinics into hospitals is noted, whereas this research is influenced by differing socio-demographic conditions in each case. Keywords: Financial Planning, Transitioning, Mother and Child Hospital